Dual functionalized chitosan based composite hydrogel for haemostatic efficacy and adhesive property. (1st November 2020) - Singh, Gopendra; Nayal, Aradhana; Malhotra, Sahil; Koul, Veena
Graphical abstract: Highlights: Hydrogel composed of functionalized chitosan (quaternized and phosphorylated chitosan), poly-Ɛ-lysine and tannic acid. Taguchi orthogonal array design was used to optimize the formulation. Functionalized chitosan and hydrogel were evaluated by FTIR, NMR, XRD, DSC and TGA. In-vitro haemostatic assays, pro-inflammatory potential, cyto-compatibility studies done. Biocompatibility and efficacy studies using Wistar rats done (Day 7, 14, and 21). Axiostat (chitosan based marketed haemostat) was used for comparative evaluation studies. Abstract: The objective of this study was to devise a dual functionalized chitosan based hydrogel dressing to control haemorrhage/ bleeding. The haemostatic hydrogel was formulated by amalgamation of a definite ratio of quaternized chitosan and phosphorylated chitosan along with tannic acid which acted as adjuvant hemostat and a crosslinker. Additionally, the hydrogel contained poly-Ɛ-lysine to impart the elastic and adhesive properties. The optimized hydrogel exhibited superior haemostatic activity (clotting time, 225 ± 5 s), platelet activation (soluble P-selectin concentration 2098 ± 150.19 ng mL −1 ), adhesion strength (almost 3 times higher in comparison to Axiostat), higher fluid absorption (approx. 14 times in 12 h) in addition to better mechanical properties, faster coagulation attributes (Prothrombin time, 12.6 s and activated partial thromboplastin time, 30.1 s) and lower proinflammatory potential (almost 3 times lower Tumor Necrosis Factor- α levels and 45 times lower InterLeukin-6 levels at 48 h against control) over marketed chitosan based dressing (clotting time, 300 ± 25 s). Cytotoxicity studies using L929 fibroblasts cells and in-vivo studies using Wistar rats confirmed that the optimized hydrogel was non-toxic, cytocompatible and biocompatible.